Developing Schemas for Assessing Social Competences among Unskilled Young People - Aarkrog, Vibe; Wahlgren, Bjarne (International Journal for Research in Vocational Education and Training, 2017)
Social competences are crucial parts of vocational education and training (VET) competences. As part of a development project preparing unskilled young people for VET, an action research project was conducted with the aim of developing a schema for assessing and grading social competences. The development included defining the social competences as well as three levels for assessing these competences. The schema was developed in cooperation with the assessors, i.e., representatives from workplaces, municipal youth guidance centres, and VET colleges. There were two main findings. First, the definitions of the competences and the levels for assessing the competences are related to the context in which the competences should be developed. Second, even though the definitions should be related to the specific contexts, to be manageable they should not be too elaborate. The aim of the project being to develop a schema that practitioners in general can use for assessing young peoples' social competences in relation to work-based training, the study concludes that further research is needed to clarify whether the schema can be used without instruction or training.